Bentall procedure as a lifesaving surgery: A single center experience. (2023) - Al-Mudhaffar, Saif S.; Alwan, Ala; Ouj, Rafid; Mowaffaq, Abdullah; Kakamad, Fahmi H.; Ahmad, Okba F.
No abstract available